Routing in opportunistic networks - Dhurandher, Sanjay Kumar; Anpalagan, Alagan; Vasilakos, Athanasios V.; Woungang, Isaac (Springer New York, 2013)
This book provides a comprehensive guide to selected topics, both ongoing and emerging, in routing in OppNets. The book is edited by worldwide technical leaders, prolific researchers and outstanding academics, Dr. Isaac Woungang and co-editors, Dr. Sanjay Kumar Dhurandher, Prof. Alagan Anpalagan and Prof. Athanasios Vasilakos. Consisting of contributions from well known and high profile researchers and scientists in their respective specialties, the main topics that are covered in this book include mobility and routing, social-aware routing, context-based routing, energy-aware routing, incentive-aware routing, stochastic routing, modeling of intermittent connectivity, in both infrastructure and infrastructure-less OppNets. Key Features: Discusses existing and emerging techniques for routing in infrastructure and infrastructure-less OppNets. Provides a unified covering of otherwise disperse selected topics on routing in infrastructure and infrastructure-less OppNets.  Includes a set of PowerPoint slides and glossary of terms for each chapter for instructors adopting it as a textbook Routing in Opportunistic Networks will be an ideal reference for practitioners and researchers working in the afore-mentioned areas. It also serves as an excellent textbook for graduate and senior undergraduate courses in communication and wireless networking research.